(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2023)
“One house, five performers, 24 hours: arrive when you can, leave when you want” – this was the synopsis of the autofictional performance Casa Vazia, a work that falls within the contagion zone between theatricality and performativity and bets so much on a space-time relationship unconventional as in the radical proximity between performers and spectators. From process materials, interviews with the cast and a bibliographic review, the article investigates how Casa Vazia established itself as a potent aesthetic-political field for the creation of bodies that vibrate, that is, bodies in experience, through the circulation, agency and negotiation of affections, memories and desires between actors, spectators, the space of the house and the territory of the city. The work contributes with reflections on the modes of operation of the contemporary scene, with emphasis on the oscillation between scene and non-scene and the experimentation of non-traditional relationships between performers and spectators.